Engineering a Chemical Switch into the Light‐driven Proton Pump Proteorhodopsin by Cysteine Mutagenesis and Thiol Modification. (13th June 2016) - Harder, Daniel; Hirschi, Stephan; Ucurum, Zöhre; Goers, Roland; Meier, Wolfgang; Müller, Daniel J.; Fotiadis, Dimitrios
Abstract: For applications in synthetic biology, for example, the bottom‐up assembly of biomolecular nanofactories, modules of specific and controllable functionalities are essential. Of fundamental importance in such systems are energizing modules, which are able to establish an electrochemical gradient across a vesicular membrane as an energy source for powering other modules. Light‐driven proton pumps like proteorhodopsin (PR) are excellent candidates for efficient energy conversion. We have extended the versatility of PR by implementing an on/off switch based on reversible chemical modification of a site‐specifically introduced cysteine residue. The position of this cysteine residue in PR was identified by structure‐based cysteine mutagenesis combined with a proton‐pumping assay using E. coli cells overexpressing PR and PR proteoliposomes. The identified PR mutant represents the first light‐driven proton pump that can be chemically switched on/off depending on the requirements of the molecular system.